Advancing plant cell wall modelling: parametric finite element approach - Takács, Ágnes; Albert, Judit (Design of Machines and Structures, 2024)
The study utilized genetic algorithms to optimize the mechanical properties of wheat stems, focusing on axial stress, shear stress, bending stress, and critical buckling force. The results indicated that the optimized stem design could withstand applied forces with adequate safety margins, enhancing lodging resistance. Future work will include advanced optimization techniques and validation to further improve wheat stem structural integrity.